Pilot-scale evaluation of Fe2O3-MgAl2O4 extrudates for chemical looping reverse water-gas shift reaction: performance and mechanical integrity - Michiel W.F. Van Cauwelaert; Lukas C. Buelens; Antoine Dechany; Iván Josipovic; Matthieu N. Boone; Hilde Poelman; Joris Proost; Vladimir V. Galvita; Kevin M. Van Geem (Chemical Engineering Journal, 2026)

Self-sealing capacity of boom clay affected by an alkaline plume: Evidences from high resolution X-ray computed tomography and hydraulic conductivity measurements - Miroslav Honty; Lander Frederickx; Ivan Josipović; Matthieu N. Boone; Pascale Senechal; Stéphane Faucher; Séverine Levasseur; Xavier Sillen (Applied Clay Science, 2025)

Multiyear Drought Strengthens Positive and Negative Functional Diversity Effects on Tree Growth Response - Hernán Serrano‐León; Haben Blondeel; Paula Glenz; Johannes Steurer; Florian Schnabel; Lander Baeten; Joannès Guillemot; Nicolas Martin‐StPaul; Georgios Skiadaresis; Michael Scherer‐Lorenzen; Damien Bonal; Matthieu Boone; et al. (Global Change Biology, 2025)
Mixed‐species forests are proposed to enhance tree resistance and resilience to drought. However, growing evidence shows that tree species richness does not consistently improve tree growth responses to drought. The underlying mechanisms remain uncertain, especially under unprecedented multiyear droughts. We used a network of planted tree diversity experiments to investigate how neighborhood tree diversity and species' functional traits influence individual tree responses to drought. We analyzed tree cores (948 trees across 16 species) from nine young experiments across Europe featuring tree species richness gradients (1–6 species), which experienced recent severe droughts. Radial growth response to drought was quantified as tree‐ring biomass increment using X‐ray computed tomography. We applied hydraulic trait‐based growth models to analyze single‐year drought responses across all sites and site‐specific responses during consecutive drought years. Growth responses to a single‐year drought were partially explained by the focal species' hydraulic safety margin (representing species' drought tolerance) and drought intensity, but were independent of neighborhood species richness. The effects of neighborhood functional diversity on growth responses shifted from positive to negative with increasing drought duration during a single growing season. Tree diversity effects on growth responses strengthened during consecutive drought years and were site‐specific with contrasting directions (both positive and negative). This indicates opposing diversity effects pathways under consecutive drought events, possibly resulting from competitive release or greater water consumption in diverse mixtures. We conclude that tree diversity effects on growth under single‐year droughts may differ considerably from responses to consecutive drought years. Our study highlights the need to consider trait‐based approaches (specifically, hydraulic traits) and neighborhood scale processes to understand the multifaceted responses of tree mixtures under prolonged drought stress. This experimental approach provides a robust framework to test biodiversity‐ecosystem functioning (BEF) relationships relevant for young, planted forests under increased drought stress.

X-ray micro-CT pipeline for large-scale tree-ring densitometry studies - Louis Verschuren; Vladimir Matskovsky; Matthieu N. Boone; Luc Van Hoorebeke; Joris Van Acker; Tom De Mil; Valerie Trouet; Charlotte Pearson; Jorden De Bolle; Toon Gheyle; Jan Van den Bulcke (Dendrochronologia, 2025)

The effect of cryopreservation on enamel microcracks – A μCT analysis using a deep learning algorithm - Noëmi M.C. De Roo; Pierre Kibleur; Liesbeth Temmerman; Ronald M.H. Verbeeck; Matthieu N. Boone; Guy A.M. De Pauw (Cryobiology, 2025)

Combining Automated Mineralogy with X-ray Computed Tomography for Internal Characterization of Ore Samples at the Microscopic Scale - Florian Buyse; Stijn Dewaele; Matthieu N. Boone; Veerle Cnudde (Natural Resources Research, 2023)

A Finite Element Method to Predict Adverse Events in Intracranial Stenting Using Microstents: In Vitro Verification and Patient Specific Case Study - Francesco Iannaccone; Matthieu De Beule; Sander De Bock; Imramsjah M. J. Van der Bom; Matthew J. Gounis; Ajay K. Wakhloo; Matthieu Boone; Benedict Verhegghe; Patrick Segers (Annals of Biomedical Engineering, 2016)